L LAYANAN BIMBINGAN KONSELING DALAM LEMBAGA PERMASYARAKATAN - Evisetiawati; Devi Aulia Tista Tista; Resiana Putri; Erica Farichatin Aida Aida; Eni Nurhasana Nurhasana; Affan Yusra Yusra (CV. Multi Kreasi Media, 2022)
Prisons are not only places to punish guilty people, but also foster prisoners to make their lives more meaningful and after leaving prison they are able to socialize with the community. research is the importance of counseling services in correctional institutions. Prisoners consist of men, women, teenagers, and children who commit crimes that violate state laws. The main role of counselors in prisons is to assist inmates in solving various kinds of prisoner problems. This research method uses content analysis on a.number.of articles that have been published in counseling journals throughout Indonesia from 2007 to 2022, with the main focus of the purpose of this research being to find out the importance of counseling guidance services in the recovery process of inmates in prisons. The biggest fear of inmates while serving their sentence is being away from their family. This is the reason for the importance of having a counselor in prison who is able to provide services in the form of counseling. It is important to practice counseling services in fostering prisoners to be able to restore their enthusiasm and passion for life. Counselors can use various ways to be able to create a comfortable atmosphere for prisoners, and make them open in expressing their problems.